Toxicity bioassay of waste cooking oil-based biodiesel on marine microalgae. (2019) - Pikula, K.S.; Zakharenko, A.M.; Chaika, V.V.; Stratidakis, A.K.; Kokkinakis, M.; Waissi, G.; Rakitskii, V.N.; Sarigiannis, D.A.; Hayes, A.W.; Coleman, M.D.; Tsatsakis, A.; Golokhvast, K.S.
Highlights: The individual components of the biodiesel had a lower toxicity threshold than in the complex mixture. The B20 sample proved to be the most toxic for the red algae P. purpureum . The B100 sample showed the highest level of toxicity for the microalgae A. ussuriensis, C. muelleri and H. akashiwo . The sample of petroleum diesel B0 showed less toxicity compared to B20 and B100. Abstract: The world biodiesel production is increasing at a rapid rate. Despite its perceived safety for the environment, more detailed toxicity studies are mandatory, especially in the field of aquatic toxicology. While considerable attention has been paid to biodiesel combustion emissions, the toxicity of biodiesel in the aquatic environment has been poorly understood. In our study, we used an algae culture growth-inhibition test (OECD 201) for the comparison of the toxicity of B100 (pure biodiesel), produced by methanol transesterification of waste cooking oil (yellow grease), B0 (petroleum diesel fuel) and B20 (diesel-biodiesel blended of 20% biodiesel and 80% petroleum diesel fuel by volume). Two marine diatoms Attheya ussuriensis and Chaetoceros muelleri, the red algae Porphyridium purpureum and Raphidophyte Heterosigma akashiwo were employed as the aquatic test organisms. A sample of biodiesel from waste cooking oil without dilution with petroleum diesel (B100) showed the highest level of toxicity for the microalgae A. ussuriensis, C. muelleri and H. akashiwo, compared to hexane, methanol, petroleum diesel (B0) and diluted sample (B20). The acute EC50 in the growth-inhibition test (96 h exposure) of B100 for the four species was in the range of 3.75–23.95 g/L whereas the chronic toxicity EC50 (7d exposure) was in the range of 0.42–16.09 g/L.